Influence of Social Media Use on The Self-Concept and Social Behaviour of Adolescents in Secondary Schools in Uasin Gishu County, Kenya - Amgechi O., Lydiah; Oseko M. , Agnes; Muyaka , Jafred (African Journal of Education,Science and Technology (AJEST), 2022)
Technological advances have been said to reduce the world into a global village thereby easing communication/interaction. By virtue of these, an online social community via the social media or Social Networking Sites (SNSs) has been birthed out. With the penetration of internet globally, billions of people are able to interact regardless of their location, race, gender or age. Young people (teenagers/adolescents) have particularly been observed to be very active on social media. The interactions and activities they engage in on social media can have either positive or negative influence on their self-concept and their social behaviour. This study therefore investigated the influence social media use on the self-concept and social behaviour of adolescents in secondary schools in UasinGishu County in Kenya. Descriptive research design was employed for the study. The study targeted students and teachers in secondary schools in Uasin Gishu County. Simple random sampling, stratified and purposive sampling were employed to yield a sample of 375 student respondents and 72 teacher respondents for the study. Questionnaires, interview schedules and focus group discussions were used for data collection. Data analysis was done with the aid of the SPSS software version 26. The study found out that in an overall sense, social media usage correlated positively with the self-concept and social behaviour of adolescents at p=0.409 and p=0.309 respectively. It concluded that social media use influenced self-concept and consequently the social behaviour of adolescents and thus recommended vigilance on the part of stakeholders and guidance and counselling to adolescents on proper use of social media.